Risco e prevalência de úlcera por pressão em idosos de instituições de longa permanência - Matos, Suellen Duarte de Oliveira (2016)
The pressure ulcers (PU) is a skin complication due to the pressure exerted on the region of bony prominence combined with friction. Objective: To analyze the risk and the prevalence of pressure ulcers in the elderly of Institutions of long permanence for the elderly in the city of Joao Pessoa. Methodology: This is a cross-sectional study, population-based and of quantitative approach, performed from the analysis of part of the database coming from the research entitled "Prevalence and Incidence of Pressure Ulcer in Institutions of Long Permanence for the Elderly in Joao Pessoa”. For the analysis of the database, the SPSS version 20.0 was used. Results: The sociodemographic data revealed that 128 (39.5%) elderly individuals were between 80- 90 years old, 244 (75.3%) were females, 289 (89.2%) single and 192 (59.3%) were institutionalized for less than five years. The prevalence of pressure ulcers corresponded to 26 cases (8%), of which 20 (77%) had only one injury, 16 (61.5%) in Stage I and 8 (30.8%) developed the lesion in the sacral region. The clinical conditions of statistically significant associations with the occurrence of PU were the variables neurological diseases (p = 0.011) and changes in vision (p = 0.005). Regarding the risk factors, fecal incontinence (p <0.001), urinary incontinence (p <0.001), cognitive deficit (p <0.007) and physical limitation (p <0.001) stood out. The strength of association evidenced by the contingency coefficient was moderate for cognitive deficit (0.375) and fecal incontinence (0.365). The results of the logistic regression model revealed that urinary incontinence increases eight times the chance of occurrence of pressure ulcers (OR = 8.805) and five times osteoarticular disorders (OR = 5,899). Conclusion: The study allowed the expansion of the knowledge about the clinical conditions, risk factors and pressure ulcers in institutionalized elderly in the capital of Paraiba, giving contributions to researches addressing the theme and to the professionals who work in these institutions, considering there is still scarcity of studies in these scenarios.